Extracting, storing, and transporting whole blood DNA under tropical conditions. Issue 7 (July 1991) - Bates, I; Bedu-Addo, G; Rutherford, T R
Abstract : A simple and robust technique for the extraction of DNA under tropical field conditions is described. It requires minimal equipment and is based on lysing cells in whole blood and precipitating the nuclei containing the DNA by centrifugation. The DNA solution can be stored in guanidinium buffer for many months without being refrigerated. Further purification of the DNA can then be carried out in a laboratory with facilities for ultracentrifugation by banding the DNA through cesium chloride. This method yields DNA of sufficient quality and purity for Southern blotting and probing and alleviates the need to transport whole blood between different countries and laboratories.